An Entropy Optimizing RAS-Equivalent Algorithm for Iterative Matrix Balancing - Chlebus, Edward; Kasapu, Viswatej (Comptes Rendus. Mathématique)
We have developed a new simple iterative algorithm to determine entries of a normalized matrix given its marginal probabilities. Our method has been successfully used to obtain two different solutions by maximizing the entropy of a desired matrix and by minimizing its Kullback–Leibler divergence from the initial probability distribution. The latter is fully equivalent to the well-known RAS balancing algorithm. The presented method has been evaluated using a traffic matrix of the GÉANT pan-European network and randomly generated matrices of various sparsities. It turns out to be computationally faster than RAS. We have shown that our approach is suitable for efficient balancing both dense and sparse matrices.